Educational podcasts and student engagement in Ecuadorian higher education: an SEM-based evaluation of the technology acceptance model - Morales-Urrutia, Diana; Yépez-Villacis, Romina; Mantilla-Falcón, Luis Marcelo (Frontiers in Education, 2026)
The integration of digital technologies has reshaped educational environments, positioning podcasts as an accessible and flexible resource that supports learning in asynchronous and multitasking contexts. In Ecuador, their adoption is challenged by the digital divide and socioeconomic inequalities, yet they also represent an opportunity to promote educational equity. This study examined the acceptance of podcasts in higher education through the Technology Acceptance Model and its relationship with student engagement. A Structural Equation Modeling approach was applied using data collected from university students, incorporating constructs such as perceived usefulness, ease of use, attitude, intention, and user experience. The model demonstrated a strong fit (CFI = 0.957; RMSEA = 0.065), confirming that perceived usefulness and ease of use significantly influence both attitude and intention to adopt. The findings suggest that podcasts constitute a strategic pedagogical tool to foster engagement, autonomy, and meaningful learning in digital higher education contexts.